Developing Islamic Nuanced Learning Module of Rectangular for Junior High School Students - Junarni, Junarni; Hidayah, Nurul; Rakhmawati, Rosida; Putra, Rizki Wahyu Yunian (Journal of Mathematical Pedagogy (JoMP), 2020)
This study aims to develop Islamic nuanced module of rectangular for junior high school students and to determine students' responses to teaching materials in the form of Islamic nuanced learning module of rectangular. This study uses research and development (R&D) methods with the ADDIE development model. There are five stages in this model, namely Analyze, Design, Development, Implementation, and Evaluation. The learning module were validated by several experts namely material experts, media experts, and religious experts. The results of the study showed that the Islamic mathematical modules on the rectangular material developed met valid and practical criteria. The validity of the module, assessed by material experts, media experts, and religious experts show respectively the percentage of 87%, 88%, and 91% which are included in the "very valid" category. The learning module are practical based on the student's practicality questionnaire in which the percentage of 92% is categorized as "very practical" category. This shows that the Islamic module nuanced on the rectangular material can be appropriately used for teaching and learning process which integrate Islamic values into mathematics learning.Keywords: Learning Module, Islamic Nuanced, Rectangular